Resistance index of the renal artery measured by doppler ultrasound as a predictor of graft function after kidney transplantation - Popović, Milica; Milić, Biljana; Petrović, Lada; Ljubičić, Bojana; Boganč, Tijana; Ćelić, Dejan (Vojnosanitetski pregled, 2022)
Background/Aim. As an optimal treatment of choice for patients with the latest stage of chronic kidney failure (CKD), renal transplantation (Tx) is performed. The resistance index (RI) of the renal artery is measured by Doppler ultrasonography routinely at certain time intervals to show the condition of the renal graft. The value of RI > 0.75 is considered abnormal. The aim of the study was to determine the correlation between the values of the RI index and the function of the transplanted kidney. Methods. We analyzed retrospectively 63 patients in whom kidney transplant was done at the Clinic for Nephrology and Clinical Immunology, the University Clinical Center of Vojvodina, Novi Sad, Serbia, in the period from 2013 to 2017. Doppler of renal blood vessels was made to all examined patients in the first month after the renal transplantation. In addition to standard demographic data, all patients had the RI index and its relationship to the function of the transplanted kidney analyzed immediately after transplantation, as well as in the 6th, 12th, and 18th month, and in a certain number of patients in the 24th and 48th month after transplantation. Results. Out of 63 patients, 63.5% were men, and 26.5% were women, with an average age of 47.67 ± 13.62 years. The primary diseases in patients which led to the terminal CKD stage were hypertension in 33.3% and different forms of glomerulonephritis; while other diseases (diabetes mellitus, chronic pyelonephritis, eclampsia, polycystic kidneys, kidney agenesia, and unknown cause) were present in a lower percentage. RI 0.75 in 27% of patients. There was no statistically significant association between RI and serum creatinine or creatinine clearance at a given time, and there was no connection between RI and gender, as well as length of previous treatment by HD. There was a statistically significant association between RI and age of kidney recipient, as well as Tx type. Conclusion. In the observed group of patients, RI of renal arteries did not prove to be a good predictor of the function of the transplanted kidney either in the early or later post-transplant periods. RI might have greater predictive significance if it were determined on or immediately after the transplantation procedure.
Keywords: graft survival; kidney transplantation; postoperative complication; prognosis; renal artery; ultrasonography; doppler.